Hypomorphic Sox10 alleles reveal novel protein functions and unravel developmental differences in glial lineages. - Wegner, Michael; Bösl, Rebecca; et al. (Development, 2007)
The transcription factor Sox10 regulates early neural crest development, specification of neural crest-derived lineages and terminal differentiation of oligodendrocytes in the central nervous system. Here, we generated two novel hypomorphic Sox10 alleles in the mouse. Mutant mice either expressed a Sox10 protein with a triple alanine substitution in the dimerization domain, or a Sox1O protein with a deletion in the central portion that we define as a cell-specific transactivation domain. Phenotypic analysis revealed important roles for a functional dimerization domain and the newly defined novel transactivation domain in melanocyte and enteric nervous system development, whereas early neural crest development and oligodendrocyte differentiation were surprisingly little disturbed in both mutants. Unique requirements were additionally detected for the novel transactivation domain in satellite glia differentiation and during Schwann cell myelination, whereas DNA-dependent dimerization was needed for immature Schwann cells to enter the promyelinating stage. These two hypomorphic alleles thus uncover novel functions of Sox10 in satellite glia and Schwann cells during late developmental stages and reveal important developmental differences between these two types of peripheral glia and oligodendrocytes regarding their reliance on Sox10.
UnivIS-Import:2015-03-09:Pub.2007.med.IB.LPCIPDBI.hypomo
Keywords: Glia; High mobility group; Neural crest; Oligodendrocyte; Satellite glia; Schwann cell; Sry